Effect of Eco-Processed Pozzolan (EPP) Mixed with Calcium Oxide to Dry Density and Physicochemical of Peat Soil - Habib Musa Mohamad; Mohd Suharmin James; Siti Nor Farhana Zakaria; Adriana Erica Amaludin; Ngui Min Fui Tom; Adnan Zainorabidin (Salehan Institute of Higher Education, 2023)
Peat is a problematic soil, and it is a common problem faced by engineers in construction. The characteristics that have been noted before are high moisture content, poor shear strength, great compressibility, and long-term settlement. For this research study, it focuses on stabilizing peat soil using EPP and CaO. There are three main tests that were conducted in this research study: index properties testing, compaction testing, and For Index Properties testing, five (5) experiments were conducted to study the index properties of disturbed peat soil, which are moisture content, fiber content, liquid limit, organic content, pH, and specific gravity. Next, for the Compaction Test, using a 4.5 kg rammer, define the optimum mixture of stabilizer that is mixed with different volumes of 5%, 10%, 15%, and 20% of stabilizer. In this study, the expected result is to inspire an in-depth study of the use of EPP material and chemical CaO as peat soil stabilizers for better utilization of problematic soil. The main finding was that the mixture with the exact amount of moisture, EPP, and CaO helped stabilize the soil and cure peat soil. Thus, this study confirms the idea of treating peat with EPP and CaO, enhancing the properties of peat soil, and sustaining the settlement over loading for a period of time accordingly. 20% mix of EPP and CaO produces the highest dry density, showing that dry density increases linearly with the amount of mixture to stabilize peat. The crystallization process between peat and EPP was pronouncedly observed where smaller particles identified as EPP filled the gaps in between the pores identified from SEM. The silicon (Si content developed from each spectrum ranged from 14.4% to 17.7%. The EDX results show significant results where mineral crystallization occurred in the coagulation process.Â Doi: 10.28991/CEJ-2023-09-07-011 Full Text: PDF